1994
DOI: 10.1007/bf00201662
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal localization of human satellites 2 and 3 by a FISH method using oligonucleotides as probes

Abstract: Classical satellites I, II and III are composed of a mixture of repeated sequences. However, each of them contains a simple family of repeated sequences as a major component. Satellites 2 and 3 are simple families of repeated sequences that form the bulk of human classical satellites II and III, respectively, and are composed of closely related sequences based on tandem repeats of the pentamer ATTCC. For this reason, extensive cross-hybridizations are probably responsible for the similar in situ hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 32 publications
(42 reference statements)
4
56
0
Order By: Relevance
“…Telomeric associations between non-acrocentric chromosomes were also recently reported (Tuck-Muller et al, 2000). Interestingly chromosomes 1, 9, and 16 contain large blocks of classical satellite long tandem repeat arrays (satellites 2 and 3) adjacent to the centromere (Tagarro et al, 1994). These regions are normally heavily methylated in somatic cells but ICF patients demonstrate a marked hypomethylation of these regions (Jeanpierre et al, 1993;Tagarro et al, 1994), indicating that DNA methylation may be essential for proper centromere structure and stability.…”
Section: Icf Syndromementioning
confidence: 84%
See 1 more Smart Citation
“…Telomeric associations between non-acrocentric chromosomes were also recently reported (Tuck-Muller et al, 2000). Interestingly chromosomes 1, 9, and 16 contain large blocks of classical satellite long tandem repeat arrays (satellites 2 and 3) adjacent to the centromere (Tagarro et al, 1994). These regions are normally heavily methylated in somatic cells but ICF patients demonstrate a marked hypomethylation of these regions (Jeanpierre et al, 1993;Tagarro et al, 1994), indicating that DNA methylation may be essential for proper centromere structure and stability.…”
Section: Icf Syndromementioning
confidence: 84%
“…Interestingly chromosomes 1, 9, and 16 contain large blocks of classical satellite long tandem repeat arrays (satellites 2 and 3) adjacent to the centromere (Tagarro et al, 1994). These regions are normally heavily methylated in somatic cells but ICF patients demonstrate a marked hypomethylation of these regions (Jeanpierre et al, 1993;Tagarro et al, 1994), indicating that DNA methylation may be essential for proper centromere structure and stability. Repetitive elements elsewhere in the genome, including a subtelomeric repeat (Kondo et al, 2000), and single copy sequences on the inactive X chromosome (Hansen et al, 2000;Miniou et al, 1994) have also been shown to undergo hypomethylation in ICF cells.…”
Section: Icf Syndromementioning
confidence: 99%
“…S1C). 15,[25][26][27][28][29] In contrast, the MIS controls showed levels of methylation in satellite II repeats that were comparable to H9 hESCs. As expected, reduced levels of methylation in the centromeric and pericentromeric regions of chromosomes 1, 9 and 16 were observed in the DNMT3B KDs compared with MIS24 hESC controls by MethylC-seq analyses ( Table 1).…”
Section: Dnmt3b Does Not Affect Early Ne Specification In Hescsmentioning
confidence: 89%
“…21,23 Although global levels of DNA methylation are only slightly reduced in ICF patients, 24 pericentromeric satellite repeat sequences on chromosomes 1, 9 and 16 are highly decondensed and hypomethylated. 15,[25][26][27][28][29] Other non-satellite repeat regions 30 and a number of genes on inactive X chromosome in female ICF patients [31][32][33][34][35] are also hypomethylated. However, in-depth genome-wide analyses of the methylation effects of DNMT3B deficiency have not been previously performed.…”
Section: Introductionmentioning
confidence: 99%
“…Previously described oligonucleotides were used as probes for satellites 2 and 3. 50 Statistics. mRNA levels are expressed as mean Ϯ SD.…”
Section: Methylation-specific Pcr and Combined Bisulfite Restriction mentioning
confidence: 99%